2023
DOI: 10.3390/metabo13010095
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Essential Oils from Piper Species (Piperaceae) against Tachyzoites of Toxoplasma gondii

Abstract: Toxoplasmosis is a tropical and neglected disease caused by the parasitic protozoa Toxplasma gondii. Conventional treatment with sulfadiazine and pyrimethamine plus folinic acid, has some drawbacks, such as inefficacy in the chronic phase, toxic side effects, and potential cases of resistance have been observed. In this study, the activity of essential oils (EOs) from three Piper species and their main constituents, including α-Pinene (Piper lindbergii and P. cernuum), β-Pinene (P. cernuum), and dillapiole (P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…For the preliminary evaluation of the 400 compounds contained in the Pandemic Box, 6-well plates were seeded with neonatal Normal Human Dermal Fibroblast cells (NHDF; Lonza, kindly donated by Dr. Sheila Nardelli, Fiocruz Paraná, Brazil) in RPMI 1640 medium supplemented with 2% Fetal Bovine Serum (Gibco), Penicillin/Streptomycin, Amphotericin B (Life Technologies, Eugene, OR, USA), and 2 mM glutamine (complete medium). After NHDF reached confluency, each well was replaced with fresh medium containing one compound at a concentration of 1 µM, and then infected with 1000 newly egressed tachyzoites from RH strain [ 29 ]. Screening at 1 μM is recommended by MMV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the preliminary evaluation of the 400 compounds contained in the Pandemic Box, 6-well plates were seeded with neonatal Normal Human Dermal Fibroblast cells (NHDF; Lonza, kindly donated by Dr. Sheila Nardelli, Fiocruz Paraná, Brazil) in RPMI 1640 medium supplemented with 2% Fetal Bovine Serum (Gibco), Penicillin/Streptomycin, Amphotericin B (Life Technologies, Eugene, OR, USA), and 2 mM glutamine (complete medium). After NHDF reached confluency, each well was replaced with fresh medium containing one compound at a concentration of 1 µM, and then infected with 1000 newly egressed tachyzoites from RH strain [ 29 ]. Screening at 1 μM is recommended by MMV.…”
Section: Methodsmentioning
confidence: 99%
“…Screening at 1 μM is recommended by MMV. As a control, infected cells were incubated with complete medium and 0.01% DMSO [ 29 ]. The plates were then kept in an incubator at 37 °C in a humid atmosphere with 5% CO 2 for seven days.…”
Section: Methodsmentioning
confidence: 99%
“…Both compounds displayed considerable toxicity against E. granulosus protoscoleces, with LC 50 values of 16.14 μM and 31.23 μM, respectively (Tabari et al., 2019). Additionally, compound 27 shows antiprotozoal and nematocidal activity (Bailén et al., 2022; Lima et al., 2021; Pacheco et al., 2022; Pereira Filho et al., 2023 ) . The compounds isofuranodiene ( 29 ) and beta‐myrcene ( 30 ) have been found to possess moderate activity against E. granulosus protoscoleces.…”
Section: Anti‐echinococcal Activity Of Terpenesmentioning
confidence: 99%
“…Studies have indicated that the essential oils from different plants exhibit low cytotoxicity and better inhibition of the proliferation of T. gondii [10,11]. Screening antiparasitic drugs from natural products from medicinal plants is an important procedure during new drug research and development [12].…”
Section: Introductionmentioning
confidence: 99%